A Brief Exit Before a Grand Entrance
Churchill has been quoted as stating “He who fails to plan, plans to fail.” Significant planning and collaboration were necessary to prepare for the first Ex-utero Intrapartum Treatment (EXIT) procedure in the IWK Health Centre in Halifax, NS. EXIT is a life-saving technique used to secure a fetal airway when there is some type of airway compression involved. The procedure is done while oxygenation and perfusion are maintained through utero-placental circulation